Analisis Faktor-Faktor Penyebab Pembiayaan Murabahah Bermasalah Bank Syariah (Studi Kasus Di Bank Syariah Mandiri KC Bintaro Tangerang) - Muhammad Said (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
Murabahah is the sale and purchase of goods at the cost of obtaining additional goods by the agreement of the seller with the purchase of goods. This murabahah is a superior contract applied to sharia financial institution products throughout the world, including Indonesia. One reason is that the murabahah contract is simpler and more manageable. However, the application of murabaha contract by Islamic banks still reaps the pros and cons of being addressed by several parties related to several issues. This study aims to determine how the internal and external factors that cause the occurrence of problematic murabaha financing at Bank Syariah Mandiri Branch Office in South Tangerang Bintaro. This research uses a qualitative approach and is descriptive — data obtained by interview and documentation. Data analysis uses the method of interaction analysis, where the data reduction component and data presentation are carried out in conjunction with the data collection process. The results showed that murabaha financing was problematic due to internal factors originating from Bank Syariah Mandiri in South Tangerang Bintaro Branch Office. Furthermore, from the customers, while external factors were caused by problems outside the customer's ability, including errors in the initial analysis and changes in the banking system, natural disasters that occur suddenly and City Government policies that often occur. Therefore the handling strategy is by standard operating procedures.